Transcranial Static Magnetic Field Stimulation over the Primary Motor Cortex Induces Plastic Changes in Cortical Nociceptive Processing - Kirimoto, Hikari; Tamaki, Hiroyuki; Otsuru, Naufumi; Yamashiro, Koya; Onishi, Hideaki; Nojima, Ippei; Oliviero, Antonio (Frontiers in Human Neuroscience, 2018)
Transcranial static magnetic field stimulation (tSMS) is a novel and inexpensive, non-invasive brain stimulation (NIBS) technique. Here, we performed non-invasive modulation of intra-epidermal electrical stimulation-evoked potentials (IES-EPs) by applying tSMS or sham stimulation over the primary motor (M1) and somatosensory (S1) cortices in 18 healthy volunteers for 15 min. We recorded EPs after IES before, right after, and 10 min after tSMS. The IES-EP amplitude was significantly reduced immediately after tSMS over M1, whereas tSMS over S1 and sham stimulation did not affect the IES-EP amplitude. Thus, tSMS may affect cortical nociceptive processing. Although the results of intervention for experimental acute pain in healthy subjects cannot be directly translated into the clinical situation, tSMS may be a potentially useful NIBS method for managing chronic pain, in addition to standard of care treatments.